A rapid and sensitive intracellular flow cytometric assay to identify Theileria parva infection within target cells - ROCCHI, M. S. (2007)
Theileria parva is an intracellular protozoan parasite transmitted by ticks that causes a fatal lymphoproliferative disease of cattle known as East Coast Fever. Vaccination against the disease currently relies on inoculation of the infective sporozoite stage of the parasite and simultaneous treatment with long-acting formulations of oxytetracycline. Sporozoites are maintained as frozen stabilates of triturated infected ticks and the method requires accurate titration of stabilates to determine appropriate dose rates. Titration has traditionally been undertaken in cattle and requires large numbers of animals because of individual variation in susceptibility to infection. An alternative tissue culture-based method is laborious and time consuming. We have developed a flow cytometric method for quantifying the infectivity of sporozoite stabilates in vitro based on the detection of intracellular parasite antigen. The method allows clear identification of parasitized cells with a high degree of sensitivity and specificity. Analysis of infected cells between 48 and 72 h post-infection clearly defines the potential transforming capability of different stabilates.